Manfaat Pengembangan Desa Wisata Wonolopo terhadap Kondisi Sosial, Ekonomi dan Lingkungan Masyarakat Lokal - Yessi Fitari; Samsul Ma'rif (Jurnal Wilayah dan Lingkungan, 2017)
Wonolopo Tourism Village is one of tourism village destinations in Semarang City.  It has three types of tourism attractions, i.e. agro-tourism, local industry and culinary, and educational tourism. The tourism potentials need to be developed to generate more benefits for the local community. The study aims to determine the benefits of the development in Wonolopo Tourism Village on social, economic, and environmental conditions of the local community. This study was conducted using both quantitative and qualitative methods through the analysis of product components of tourism village to find out the strengths and weaknesses in the development of tourism products in Wonolopo, and Anova analysis to determine the alteration of local community condition due to the tourism village development. The results show that the development of Wonolopo Tourism Village has moderate impact on the social, economic and environmental aspects to the local community. In the social aspect, the artistic potential had increasingly to be preserved and become the local wisdom. In the economic aspect, the development of tourism village has increased the local livelihood and local business opportunity. In the environmental aspect, the tourism village has improved the village infrastructures and accessibility condition.